Sciatic Nerve Block in Single Nerve Block Technique for Unilateral Foot Surgery - an Alternative to Spinal Anaesthesia - Haque, Mozibul; Hussain, Muhammad Delwar; Faruquee, Md Zulfiker Ali; Alam, Md Rabiul; Islam, Md Zahedul (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: In lower extremity surgeries, central neuraxial block or peripheral regional anesthesia technique can be used, mainly in elderly patients. This study investigates the efficiency of spinal anesthesia and sciatic nerve block techniques in lower extremity surgery. Spinal anesthesia may impair hemodynamic stability; peripheral nerve blocks targeting the sciatic nerve may be a useful alternative. Objective: To compare Unilateral Spinal Anesthesia versus Popliteal Block in patients undergoing elective foot surgery to determine the method of better outcome. Patients and Methods: This randomized comparative study was carried out on fifty co-operative patients of both sexes who were scheduled for elective foot surgeries. According to the used method of regional anesthesia, patients were divided into: (S) group unilateral intrathecal block with low-dose (7.5mg) of hyperbaric bupivacaine plus intrathecal fentanyl (25 mcg) and (P) group in which the sciatic nerve at the popliteal fossa was blocked via posterior approach by injecting 20ml 0.5% bupivacaine (100mg). The difficulty of the block performance, level of patient discomfort, block performance time, onset of sensory and motor blocks, time in hours to the first request for supplemental systemic analgesia postoperatively, its total consumption for 24 hours postoperatively and associated side effects were recorded in each group. Results: Statistically, it was found no significant differences between the demographic characteristics as well as the duration of surgery between the groups. The groups did differ significantly in the difficulty of the block performance. However, a longer duration for performing the block was observed in the P group. The level of patient discomfort was significantly lesser in the P group. The onset of complete sensory block was significantly longer in the P group. Hemodynamic profiles of our patients were found to be remarkably stable throughout the intraoperative period. In the P group, the time to first pain medication was significant longer. Moreover, the total dosage of analgesics during the first 24 hours postoperatively in group P was highly significant lesser compared to the other groups. Conclusion: Sciatic nerve block at the popliteal fossa is an ideal alternative where it is preferable to avoid spinal anesthesia for foot surgeries in haemodynamicaly unstable patients. J Bangladesh Coll Phys Surg 2019; 37(4): 181-185